WORKSHOP PEMETAAN POTENSI SISWA MELALUI ANALISA TULISAN TANGAN DAN TANDA TANGAN BAGI GURU BK SMA SE-KABUPATEN MAJALENGKA - Syamsul Arif Billah; Atef Fahrudin, Hanifa K. Syahida, Gilang Nurman Sonjaya (JOURNAL OF COMMUNITY DEDICATION, 2023)
The guidance counselor's role in unlocking students' potentials is emphasized in this summary. Students often lack the awareness of how to identify their own potential, making it crucial for counselors to possess the skill of mapping potential through handwriting analysis and signatures, acquired through workshops. The workshop involves stages of preparation, implementation, and evaluation, employing lecture, discussion, and practical exercises. Recognizing the complexity of the issue, the study advocates for well-planned meetings to ensure deep and effective learning. Post-test results indicate the success of the workshop in imparting basic knowledge about the importance of counselors' understanding in mapping students' potential. Regularly scheduled activities are planned to provide ongoing, practical knowledge for teachers to assist students in continuous potential mapping.